Effect of dairy matrices on the survival of Streptococcus thermophilus, Brevibacterium aurantiacum and Hafnia alvei during digestion. (October 2017) - Hernández-Galán, Leticia; Cattenoz, Thomas; Le Feunteun, Steven; Canette, Alexis; Briandet, Romain; Le-Guin, Sylvia; Guedon, Eric; Castellote, Jessie; Delettre, Jerome; Dugat Bony, Eric; Bonnarme, Pascal; Spinnler, Henry Eric; et al.
Abstract: This study evaluated the ability of dairy matrices, different in composition (with and without fat) and structure (liquid and gel), to enhance microorganisms survival through digestion. The viability of three dairy microorganisms Streptococcus thermophilus, Brevibacterium aurantiacum and Hafnia alvei was measured during in vitro and in vivo digestion. S . thermophilus was highly sensitive to gastric stress, and was not found in the duodenal compartment. B . auranticum was moderately sensitive to gastric stress but resistant to duodenal stress. H . alvei was highly resistant to both stresses. LIVE/DEAD confocal microscopy's images, probed the effect of low pH on microorganisms survival. However, in vivo analyses (16S rRNA gene metabarcoding) failed to confirm in vitro observations since tested microorganisms were not detected. Despite of the different evolutions during digestion on buffer capacity, lipolysis, and rheological characteristics, we did not observe any protective effect of the dairy matrices on microorganisms survival. Graphical abstract: Highlights: Stomach acidification was the main cause of microorganism mortality. Dairy matrix structure and composition had no influence on microorganisms survival. Resistance of microorganisms to digestive stress was strain-dependent.